Power relationships in the lower track science classrooms : how students "own" teachers - Muhammad Danial Ahmad Sufyan (Nanyang Technological University, 2020)
This paper presents an analysis of the power relationships in a particular lower track science classroom of a secondary school in Singapore. We aim to understand the power relationships that arise out of student-teacher interactions in the classroom. In the everyday classroom, students constantly attempt at undermining the authority of their teachers. These attempts are what we will term as ‘owning’. The sociological framework we use to frame our analysis is through symbolic interactionism. This framework will allow us to understand how two teachers of varying experiences engage ‘face-work’ to manage owning. Through (in)correct lines of action, the owning will consequently succeed or fail. Analysis of interviews with the two teachers, their students and video recordings of their lessons will shed light on how owning is more than just unidimensional and indeed, contains nuances that can only be studied through the symbolic interactionist perspective. By correctly managing different facets of owning, these attempts could enhance rapport and mutual respect between student and teacher. The findings show the many complexities that lie in educational pedagogy of today and by studying owning, we hope to provide teachers, old and new, with alternative ways to look at and manage classroom authority.